Indonesian leadership in the global organization of Parliamentarians Against Corruption (GOPAC) and its impact on the institutionalization of Open Parliament in Indonesia - Zon, Fadli; Andika, Muhammad Tri (Universiti Utara Malaysia Press, 2021)
The Open Parliament Indonesia (OPI) declaration in 2018 was a pivotal moment in the democratization of the Indonesian parliament. The OPI declaration marked a strategic achievement of Indonesia’s parliamentary diplomacy. At a time when the public trust towards the Indonesian parliament was low, the OPI declaration opened a new chapter for the Indonesian parliament to revitalize its commitment toward increasing public trust. It is worth noting that the decision of the Indonesian parliament to join the open parliament initiative began with its leadership in the Global Organization of Parliamentarians Against Corruption (GOPAC). This article has addressed the key question of how the Indonesian parliament’s leadership in GOPAC contributed to the establishment of Open Parliament Indonesia and further argued that Indonesia’s leadership in international organizations such as GOPAC has influenced Indonesian parliamentary behaviour. This has been achieved by creating room and access for the parliament to intensely engage with issues of open parliament in the international fora. It marked the compliance of the Indonesian parliament with international norms, demonstrating its commitment to adhere to the global democratic principles of transparency, openness and accountability. International norms prompted by GOPAC’s open parliament advocacy has affected Indonesia’s parliament’s policy choice as regards the open parliament agenda. Indonesia’s leadership in GOPAC, represented by the Deputy Speaker in Politics, Law and Security as GOPAC president, accelerated the institutionalization of the OPI.